Plato's Republic an Edinburgh philosophical guide - Sheppard, Darren, 1969- (Edinburgh philosophical guides series., 2009)
Everything you need to know about Plato's Republic in one volume.This book will introduce students to Plato's Republic and facilitate the reader's own dialogue with it, without providing an interpretation or a response on the reader's behalf. Alongside a passage-by-passage commentary on the text, D.J. Sheppard highlights many of the central interpretative challenges faced by the reader and surveys a range of possible responses to them. Designed to be read alongside Plato's text, this approach will be helpful for students and lecturers alike.